Human serum promotes Candida albicans biofilm growth and virulence gene expression on silicone biomaterial. - Yuthika Hemamala Samaranayake; Becky P K Cheung; Joyce Y Y Yau; Shadow K W Yeung; Lakshman P Samaranayake (PLoS ONE, 2013)
OBJECTIVES: Systemic candidal infections are a common problem in hospitalized patients due to central venous catheters fabricated using silicone biomaterial (SB). We therefore evaluated the effect of human serum on C. albicans biofilm morphology, growth, and the expression of virulence-related genes on SB in vitro. METHODS: We cultivated C. albicans SC5314 (wild-type strain, WT) and its derivative HLC54 (hyphal mutant, HM) for 48 h in various conditions, including the presence or absence of SB discs, and human serum. The growth of planktonic and biofilm cells of both strains was monitored at three time points by a tetrazolium salt reduction assay and by scanning electron microscopy. We also analyzed by RT-PCR its expression of the virulence-related genes ALS3, HWP1, EAP1, ECE1, SAP1 - SAP10, PLB1, PLB2, PLC and PLD. RESULTS: At each time point, planktonic cells of WT strain cultured in yeast nitrogen base displayed a much higher expression of EAP1 and HWP1, and a moderately higher ALS3 expression, than HM cells. In planktonic cells, expression of the ten SAP genes was higher in the WT strain initially, but were highly expressed in the HM strain by 48 h. Biofilm growth of both strains on SB was promoted in the presence of human serum than in its absence. Significant upregulation of ALS3, HWP1, EAP1, ECE1, SAP1, SAP4, SAP6 - SAP10, PLB1, PLB2 and PLC was observed for WT biofilms grown on serum-treated SB discs for at least one time point, compared with biofilms on serum-free SB discs. CONCLUSIONS: Human serum stimulates C. albicans biofilm growth on SB discs and upregulates the expression of virulence genes, particularly adhesion genes ALS3 and HWP1, and hydrolase-encoding genes SAP, PLB1 and PLB2. This response is likely to promote the colonization of this versatile pathogen within the human host.